Servant Leadership, Work Ability, And Work Discipline in Shaping Employee Performance: Evidence from PT Bali Chocolate Sanur, Denpasar, Bali - Ni Kadek Wulan Indriyani; I Wayan Sukadana; I Wayan Widnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
A company cannot grow without high employee performance. Performance refers to actual performance, work achievements, or tangible accomplishments made by employees, which comes from the term job performance. One way to measure employee competence is by looking at their work performance. The success of an organization is directly proportional to the quality of its human resources. Conversely, poor human resource performance can lead to poor organizational performance. Sales realization data shows that most months in 2024 at PT Bali Chocolate Sanur Denpasar did not meet expectations, indicating a decline in employee performance. Therefore, a reference, such as a benchmark or determinant, is needed to assess employee performance. At PT Bali Chocolate Sanur Denpasar, we hope to find out how servant leadership, work aptitude, and work discipline affect productivity. A quantitative approach was used for this topic. Using a census sampling technique, the total number of employees at PT. Bali Chocolate Sanur, which is 55 people, became the population. Questionnaires, interviews, and observations were the tools used to collect data. The data was analyzed using multiple linear regression. Based on the results of the study, among other things: Servant leadership, work aptitude, and work discipline will have a positive and substantial impact on company profits. Leadership quality, work ability, and work discipline are three areas that can always be improved by the management of PT. Bali Chocolate Sanur Denpasar to improve employee performance.